TRIM32 ubiquitin E3 ligase, one enzyme for several pathologies: From muscular dystrophy to tumours. - Lazzari, Elisa; Meroni, Germana (Int J Biochem Cell Biol, 2016)
TRIM32 is a member of the TRIpartite Motif family characterised by the presence of an N-terminal three-domain-module that includes a RING domain, which confers E3 ubiquitin ligase activity, one or two B-box domains and a Coiled-Coil region that mediates oligomerisation. Several TRIM32 substrates were identified including muscular proteins and proteins involved in cell cycle regulation and cell motility. As ubiquitination is a versatile post-translational modification that can affect target turnover, sub-cellular localisation or activity, it is likely that diverse substrates may be differentially affected by TRIM32-mediated ubiquitination, reflecting its multi-faceted roles in muscle physiology, cancer and immunity. With particular relevance for muscle physiology, mutations in TRIM32 are associated with autosomal recessive Limb-Girdle Muscular Dystrophy 2H, a muscle-wasting disease with variable clinical spectrum ranging from almost asymptomatic to wheelchair-bound patients. In this review, we will focus on the ability of TRIM32 to mark specific substrates for proteasomal degradation discussing how the TRIM32-proteasome axis may (i) be important for muscle homeostasis and for the pathogenesis of muscular dystrophy; and (ii) define either an oncogenic or tumour suppressive role for TRIM32 in the context of different types of cancer.